The effect of some growth regulators on the micro propagation of orchid (Phalaenopsis philippinensis) by flowering stem buds - Mehdi Khorshidi (فیزیولوژی محیطی گیاهی, 2022)
Orchids are one of the most famous and important ornamental plants that have a high commercial value. plant tissue culture is one of the most important methods for the plant proliferation. The aim of this study was to determine the best concentration of growth regulators of benzyl amino purine (BAP) and indole butyric acid (IBA) on orchid micro propagation. The flower stem buds of orchid (Phalaenopsis philippinensis) were used as explant. This study was performed as a factorial in a completely randomized design with two factors BAP, IBA and in three replications. In the stem formation section of the first factor BAP at 4 levels (0, 0.5, 1 and 2 mg/l) and IBA at 2 levels (0 and 0.25 mg/l), also in the root formation section the first factor IBA in 4 levels (0, 0.5, 1 and 2 mg/l) and BAP were considered at 2 levels (0 and 0.1 mg/l). The results of this study showed that the highest number of shoot formation was obtained at the concentration of 1 mg/L BAP with 0.25 mg/L IBA which has led to the production of 12.27 shoot per explant. The lowest number of shoot formation was observed in the group control. In the root formation, the highest number of roots (4.33) and also the maximum root length (8.67 cm) were obtained at the concentration of 1 mg/L IBA with 0.1 mg/L BAP. The results also show that the combination of growth regulators together improves the result in comparison with their uses alone. Therefor results generally shows that the plant tissue culture is a suitable and optimal way to propagate orchid species.